Evaluation of the Cerebroprotective Properties of Ademol-gel in the Analysis of Specific Indicators in the Open Field Test - Semenenko, S.; Semenenko, I.; Burlaka, B. S.; Samura, I. B.; Bukhtiyarova, N. V.; Ryzhenko, V. P.; Khromylova, O. V.; Бурлака, Богдан Сергійович; Самура, Ірина Борисівна; Бухтіярова, Ніна Вікторівна; Риженко, Віктор Павлович; Хромильова, Ольга Володимирівна (My University, 2023)
Experimental subarachnoid hemorrhage (SAH) modeling in rats led to a significant, by 3 times, decrease in the total activity of animals, a decrease in the distance traveled by 2 times, a significant increase in inactivity when moving from the dark field to the illuminated part by 2 times, indicating a decrease in locomotor and search activity. SAH did not affect the number of unsupported rearing, but led to an increase in supported rearing against the wall, and a decrease in the number of short grooming acts against the background of an unchanged amount of long grooming. This behavior also testified to increased anxiety, excitability, irritability of animals, discomfort, and depression. The intranasal introduction of Ademol-gel at a dose of 2 mg/kg (a developed original intranasal form) to animals with SAH contributed to the positive emotional status and behavior of rats in the open field test, as evidenced by a decrease in anxiety, aggressiveness, and depressive behavior against the background of increased comfort and empathy in animals. Against the background of the intranasal introduction of Ademol-gel, the processes of restoring general motor and exploratory activity in animals after SAH were also accelerated. Nimodipine (30 μg/kg) was inferior to Ademol in terms of the degree of influence on the studied parameters of animal behavior. The results are an experimental justification for further study of a new dosage form – Ademol intranasal gel.
Keywords: Ademol; Cognitive Deficit; Subarachnoid Hemorrhage